Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1264/jsme2.me10184
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Diversity of Anaerobic Ammonium Oxidation (Anammox) Bacteria in the Sediment of a Eutrophic Freshwater Lake, Lake Kitaura, Japan

Abstract: Although the emission of N2 via anaerobic ammonium oxidation (anammox) is a key process in the elimination of nitrogenous compounds from aquatic environments, little information is available regarding its significance and the relevant microorganisms (anammox bacteria) in eutrophic freshwater lakes. In the present study, the anammox bacteria in the sediment of a eutrophic lake in Japan, Lake Kitaura, were examined using a 15 N-tracer technique to measure their potential anammox activity. Potential anammox activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 34 publications
8
82
0
Order By: Relevance
“…The five predominant genera of anammox bacteria identified in this study (see above) have been observed in many habitats, including soils (Humbert et al, 2010;Wang et al, 2012b;Hu et al, 2013;Wang and Gu, 2013) and sediments (Zhang et al, 2007;Yoshinaga et al, 2011). Similar to previous reports, Candidatus Brocadia dominated in this paddy soils fields (Bai et al, 2015;Yang et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The five predominant genera of anammox bacteria identified in this study (see above) have been observed in many habitats, including soils (Humbert et al, 2010;Wang et al, 2012b;Hu et al, 2013;Wang and Gu, 2013) and sediments (Zhang et al, 2007;Yoshinaga et al, 2011). Similar to previous reports, Candidatus Brocadia dominated in this paddy soils fields (Bai et al, 2015;Yang et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…High variability was also observed in a study of potential anammox rates in the water column of Sandusky Bay and Lake Erie (Lu et al, 2018). Marked variability may be characteristic of anammox activity in freshwater environments, even across small spatial and temporal scales (Yoshinaga et al, 2011;Zhu et al, 2013Zhu et al, , 2015. Anammox made up an average of 14 % of sediment N removal across the sampling period, indicating that anammox activity in Sandusky Bay may be typical of shallow estuarine and freshwater systems (Thamdrup and Dalsgaard, 2002;Dalsgaard et al, 2005;Schubert et al, 2006;Dong et al, 2009;Hsu and Kao, 2013;McCarthy et al, 2016).…”
Section: N Removal Processesmentioning
confidence: 82%
“…Dissimilatory microbial processes may also consume DIN in sediments, representing pathways of permanent N removal whereby N leaves the system as N 2 . Denitrification is expected to be the dominant microbial N removal pathway in freshwaters (Seitzinger et al, 2006), although anammox, a competing pathway, has not been extensively studied in freshwater systems (Yoshinaga et al, 2011;Zhu et al, 2013). Nitrous oxide (N 2 O), a potent greenhouse gas, is a byproduct of denitrification and nitrification (Wrage et al, 2001) and is a detrimental consequence of microbial N removal.…”
Section: Introductionmentioning
confidence: 99%
“…Marked variability may be characteristic of anammox activity in freshwater environments, even across small spatial and temporal scales (Yoshinaga et al, 2011;Zhu et al, 2013;. typical of shallow estuarine and freshwater systems (Thamdrup and Dalsgaard, 2002;Dalsgaard et al, 2005;Schubert et al, 2006;McCarthy et al, 2016).…”
Section: N Removal Processesmentioning
confidence: 99%
“…Denitrification is expected to be the dominant microbial N removal pathway in freshwaters (Seitzinger et al, 2006), although anammox, a competing pathway, has not been extensively studied in freshwater systems (Yoshinaga et al, 2011;Zhu et al, 2013). Nitrous oxide (N2O), a potent greenhouse gas, is a byproduct of denitrification and nitrification (Wrage et al, 2001) and is a detrimental consequence of microbial N removal.…”
Section: Introduction 25mentioning
confidence: 99%